Combined Large-N Seismic Arrays and DAS Fiber Optic Cables across the Hengill Geothermal Field, Iceland - Obermann, Anne; id_orcid:0 000-0001-6933-6301; Sánchez Sánchez-Pastor, Maria Del Pilar; id_orcid:0 000-0002-1163-5488; Wu, Sin-Mei; id_orcid:0 000-0001-8330-471X; Wollin, Christopher; Baird, Alan F.; Isken, Marius Paul; Clinton, John Francis; id_orcid:0 000-0001-8626-2703; Goertz-Allmann, Bettina P.; et al. (Seismological Research Letters, 2022)
ISSN:0895-0695 ISSN:1938-2057